Incidence of Pulmonary Arterial Hypertension in Patients with Psoriasis: A Retrospective Cohort Study - Choi, Young M (Perm J, 2017)
CONTEXT: Inflammatory signaling may play an important role in the pathogenesis of pulmonary arterial hypertension (PAH). OBJECTIVE: To assess the incidence of PAH in patients with mild and severe psoriasis compared with their respective controls. DESIGN: From January 2004 to November 2012, we performed a retrospective cohort study of patients with psoriasis in the Kaiser Permanente Southern California Health Plan. Patients with an International Classification of Diseases, Ninth Revision Clinical Modification diagnostic code for psoriasis (696.1) or psoriatic arthritis (696.0) without a prior diagnosis of primary PAH (416.0) or secondary PAH (416.8) were eligible for inclusion. Patients who had never received a diagnosis of psoriasis were frequency-matched by age, sex, and race to form the control cohorts. MAIN OUTCOME MEASURES: Incidence of PAH in patients with psoriasis compared with matched controls. RESULTS: There were 10,115 patients with mild psoriasis, 3821 with severe psoriasis, and 69,360 matched controls. On multivariable analysis, there was a significantly increased risk of PAH developing in the severe psoriasis cohort vs their controls (hazard ratio = 1.46, 95% confidence interval = 1.09–1.94). CONCLUSION: The systemic inflammatory process underlying psoriasis may be a cause for an increased risk of PAH, but there are numerous secondary causes of PAH, some of which were not accounted for in our study. Further prospective, randomized controlled trials are necessary to establish psoriasis as a risk factor for PAH.